(untitled) (Scientific journal of the Fergana State University, 2023)
A number of projects have been introduced in order to increase the higher education quality and meet the urgent demands in the job market in the last few years. The present research is also related to higher education, namely, language teaching at Namangan State University. The present proposal planned to put forward is to teach a specially-designed EAP course to Biology students and the article discusses the importance of EAP course for the target students and the recommended course organisation.